Optimalisasi kinerja guru melalui manajemen sekolah dan budaya organisasi di Kabupaten Kepulauan Meranti - Syah, Syahrial; Supiani (Karoteh Utama, 2024)
This study explores the influence of school management and organizational culture on the performance of junior high school teachers in the Meranti Islands Regency. A quantitative approach was employed, involving 143 civil servant teachers from 41 junior high schools as the sample. Data were collected through questionnaires and analyzed using regression methods to examine the relationship between the independent variables (school management and organizational culture) and the dependent variable (teacher performance). The results revealed that school management and organizational culture collectively have a significant impact on teacher performance. The F-value (8.945) was greater than the F-table value (2.67) with a significance level of 0.000 (< 0.05). These findings confirm that both variables significantly influence teacher performance when combined. The study is limited to civil servant teachers in the Meranti Islands Regency, and its results may not be generalizable to other regions or teachers with different employment statuses. The findings have practical implications for school administrators and policymakers to enhance teacher performance through improvements in school management, organizational culture, and workload management. Additionally, the study contributes to the literature on factors influencing teacher performance in remote areas, which remains an under-researched topic.